Riqualificazione della Collina di Pentimele - Nasti, Paola; Guarnaccia, Franco; Maltese, Filippo (GEOmedia, 2010)
Requalification of Pentimele hill 2010 has been a year fulfilled with successes for the Reggio Calabria High School for Surveyors 'A. Righi'. For the fourth time the school won a prize, during the last edition of ASITA, for its educational activities and especially, for the on field experience carried out on the Pentimele hill, near Reggio Calabria.